Variation in occurrence of equatorial plasma bubbles (EPBs) using All Sky Imager from low latitude station Kolhapur (16.8 °N, 74.2 °E, 10.6° dip. Lat.). Issue 11 (1st December 2017) - Sharma, A.K.; Gurav, O.B.; Chavan, G.A.; Gaikwad, H.P.; Ghodpage, R.N.; Patil, P.T.
Abstract: All Sky Imager (ASI) data of over 351 nights with OI 630.0 nm emission recorded during 2011 to 2015 (increasing phase of 24 th solar cycle) are analyzed to study the percentage occurrence of EPBs. The ASI is installed at low latitude station Kolhapur (16.8 °N, 74.2 °E, 10.6° dip. Lat.) which has 140° field of view (FOV). In this paper we have studied hourly, daily, seasonal and yearly percentage of occurrence of EPBs and their variation with solar and magnetic activity. The EPBs onset occurs at around 20:00 IST and extends towards dawn with a peak around midnight. We analyzed all the disturbed nights (Ap > 18) from the period of 2011 to 2015 and observed that the magnetic activity suppresses the occurrence of EPBs. Also the EPBs are fairly correlated with solar activity (10.7 cm solar flux).